2013
DOI: 10.1213/ane.0b013e3182863c22
|View full text |Cite
|
Sign up to set email alerts
|

Regional Scalp Block for Postcraniotomy Analgesia

Abstract: Published RCTs of RSB are small and of limited methodological quality but meta-analysis shows a consistent finding of reduced postoperative pain. This evidence supports the use of RSB for patients undergoing craniotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
134
0
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(155 citation statements)
references
References 29 publications
5
134
0
16
Order By: Relevance
“…In contrast, pre-incisional ultrasound-guided ilioinguinal/iliohypogastric nerve blocks did not reduce EA after ambulatory paediatric hernia repair, although nerve block decreased the amount of intraoperative sevoflurane needed. 1 The single intravenous injection of remifentanil 1 lg/kg that was administered just prior to skin incision in the remifentanil group was enough to achieve an end-tidal concentration of sevoflurane during surgery comparable with that in the block group. A pre-incisional blockade of the major scalp nerves and/or infiltration of anaesthesia around the nevi can block nociceptive pain arising from the wound completely for a few hours.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, pre-incisional ultrasound-guided ilioinguinal/iliohypogastric nerve blocks did not reduce EA after ambulatory paediatric hernia repair, although nerve block decreased the amount of intraoperative sevoflurane needed. 1 The single intravenous injection of remifentanil 1 lg/kg that was administered just prior to skin incision in the remifentanil group was enough to achieve an end-tidal concentration of sevoflurane during surgery comparable with that in the block group. A pre-incisional blockade of the major scalp nerves and/or infiltration of anaesthesia around the nevi can block nociceptive pain arising from the wound completely for a few hours.…”
Section: Discussionmentioning
confidence: 93%
“…13 However, effect of postoperative pain relief by regional anaesthesia 6 previously reported that pre-incisional infraorbital nerve block decreased the incidence of EA effectively in children who underwent cleft lip surgery, but authors assumed that besides pain relief, the reduced amount of sevoflurane by nerve block during surgery might be an important factor in reducing the incidence of EA. 1 The scalp nerve block is a simple technique that can be performed rapidly, safely, and reliably. 14 In this study, we were able to maintain similar, end-tidal concentrations of sevoflurane during surgery, without a significant fluctuation of blood pressure, in both the remifentanil and block groups.…”
Section: Discussionmentioning
confidence: 99%
“…, Guilfoyle et al . ). Although pharmacological interventions exist, no one therapeutic medication has been identified as most efficacious (National Pharmaceutical Council , Paolino et al .…”
Section: Discussionmentioning
confidence: 97%
“…The pulsating or pounding headache that occurs in about two-thirds of patients undergoing a craniotomy [9,23] could result from damage to extracranial periosteal afferents, given that this headache can be alleviated by regional scalp nerve block [12,23]. The sensory innervation of the calvarial periosteum may also contribute to the development and maintenance of other calvarial-related head pain such as following head trauma.…”
Section: Discussionmentioning
confidence: 99%